Effects of corticosteroids on COPD lung macrophage phenotype and function. Issue 7 (7th April 2020) - Higham, Andrew; Scott, Tom; Li, Jian; Gaskell, Rosemary; Dikwa, Aisha Baba; Shah, Rajesh; Montero-Fernandez, M. Angeles; Lea, Simon; Singh, Dave
Abstract: The numbers of macrophages are increased in the lungs of chronic obstructive pulmonary disease (COPD) patients. COPD lung macrophages have reduced ability to phagocytose microbes and efferocytose apoptotic cells. Inhaled corticosteroids (ICSs) are widely used anti-inflammatory drugs in COPD; however, their role beyond suppression of cytokine release has not been explored in COPD macrophages. We have examined the effects of corticosteroids on COPD lung macrophage phenotype and function. Lung macrophages from controls and COPD patients were treated with corticosteroids; effects on gene and protein expression of CD163, CD164, CD206, MERTK, CD64, CD80 and CD86 were studied. We also examined the effect of corticosteroids on the function of CD163, MERTK and cluster of differentiation 64 (CD64). Corticosteroid increased CD163, CD164, CD206 and MERTK expression and reduced CD64, CD80 and CD86 expression. We also observed an increase in the uptake of the haemoglobin–haptoglobin complex (CD163) from 59 up to 81% and an increase in efferocytosis of apoptotic neutrophils (MERTK) from 15 up to 28% following corticosteroid treatment. We observed no effect on bacterial phagocytosis. Corticosteroids alter the phenotype and function of COPD lung macrophages. Our findings suggest mechanisms by which corticosteroids exert therapeutic benefit in COPD, reducing iron available for bacterial growth and enhancing efferocytosis.